ANALISA PERBANDINGAN DRIVER LED TOPOLOGI LINIER DAN SWITCHING - Slamet Riyadi (Jurnal Elektra, 2019)
Current technological developments are much faster than previous periods, so with the use of lighting at this time many types of lights are used for lighting installations. One type of lamp that is popular is LED lights, LEDs have many advantages compared to other lights. However, the LED requires a controller or driver so that the LED can turn on stable and emit maximum light. There are many types of drivers on the market and many literatures that discuss this LED driver. In this paper we discuss two types of LED driver circuit topologies, namely passive or linear topology and active topology or Switching. Analysis of the two types of topologies includes the level of output stability with respect to the rise and decrease in the input voltage and the intensity of the light emitted by each controller.